Square supramolecular assemblies of uranyl complexes in organic solvents. Issue 72 (20th August 2018) - Servis, Michael J.; Wu, David T.; Shafer, Jenifer C.; Clark, Aurora E.
Abstract : Uranyl, ligand and solvent interactions lead to unique supramolecular assembly. Abstract : Uranyl nitrate/extractant complexes form long-range isotropic pairs and short-range ordered dimeric assemblies with a unique square configuration comprised of noncovalent ligand and acid anion mediated interactions, further stabilized by organic phase solvation.